PEMAHAMAN KONSEP MATEMATIKA SISWA PADA PEMBELAJARAN PERAIHAN KONSEP - Syahfitri, Lely; Ristontowi, Ristontowi (Jurnal Math-UMB.EDU, 2016)
The background of this research is caused many things should be considered in learning mathematics one of them is students should be have ability in understanding concept of learning mathematics. Because each lesson of math materials contain a number of concepts that should be understand by students, therefore students should be able to relate what they have in their thinking structure like a mathematical concepts with the problems of students face. This Research aims to know picture students ability of mathematical concepts in VII class SMP PGRI Bengkulu city using lesson model of attainment concept on reflection material and what the factors that influence it. In this research, the data collection is done with tests and interviews.This research is a qualitative research descriptive . This study done in May 2015 at junior high school PGRI Bengkulu city. Sources of data are all of VIIth grade students. Data capabilities student in understanding mathematical concepts obtained using tests and interviews. Data tests students' ability of understanding mathematical concepts analyzed descriptively according Miles and Huberman. And then total four students were interviewed to find out more how the students' understanding of mathematical concepts.The results showed there were 21 students from 25 students were categorized good and 3 students were categorized enough, and a student were categorized less, so overall students' abilities in understanding mathematical concepts using models attainment concepts of mathematical students by using model attainment concept in VIIth class Â SMP PGRI Bengkulu City are categorized good.Â Keywords: the ability of understanding mathematical concepts, learning model of attainment conceptÂ